Pengaruh Literasi Keuangan Syariah, Religiusitas, dan Kepercayaan Terhadap Minat Menabung Di Bank Syariah - Anita Zulaecha; Zainal Alim Adiwijaya (Politeknik Raflesia Press, 2025)
This study aims to analyze the effect of Islamic financial literacy, religiosity, and trust on interest in saving in Islamic banks. The population in this study were Islamic bank customers in Demak Regency, and sampling using purposive sampling technique so that the sample in this study amounted to 100 respondents. This study uses data obtained from primary data sources, namely the type of data source obtained directly from respondents using the questionnaire method. This research data was analyzed using multiple linear regression analysis methods. The results of this study indicate that Islamic financial literacy and trust have a positive and significant effect on interest in saving in Islamic banks, while religiosity has no significant effect on interest in saving in Islamic banks.